2020
DOI: 10.1113/ep088629
|View full text |Cite
|
Sign up to set email alerts
|

Task‐specific strength increases after lower‐limb compound resistance training occurred in the absence of corticospinal changes in vastus lateralis

Abstract: Neural adaptations subserving strength increases have been shown to be task-specific, but responses and adaptation to lower-limb compound exercises such as the squat are commonly assessed in a single-limb isometric task. This two-part study assessed neuromuscular responses to an acute bout (Study A) and 4 weeks (Study B) of squat resistance training at 80% of one-repetition-maximum, with measures taken during a task-specific isometric squat (IS) and non-specific isometric knee extension (KE). Eighteen healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 88 publications
(123 reference statements)
2
20
5
Order By: Relevance
“…Meta-analytic evidence suggests that RT increase CSE in the trained limb when measured during contraction, 36 but do not change in the untrained limb. 10 However, our results do not support the role of an increased CSE as a mechanism to improve force in either leg, which agrees with previous studies that also found no changes 17,18,37 or even decreases 38 in CSE when measured at rest and during contraction in the trained limb, or no changes at rest or during contraction in the untrained limb. 10 Reductions in CSE in the trained muscles after a short-term RT have been suggested to be related to an increase in corticospinal efficiency that reduces the neural resources needed to perform the task during which measurements are obtained.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Meta-analytic evidence suggests that RT increase CSE in the trained limb when measured during contraction, 36 but do not change in the untrained limb. 10 However, our results do not support the role of an increased CSE as a mechanism to improve force in either leg, which agrees with previous studies that also found no changes 17,18,37 or even decreases 38 in CSE when measured at rest and during contraction in the trained limb, or no changes at rest or during contraction in the untrained limb. 10 Reductions in CSE in the trained muscles after a short-term RT have been suggested to be related to an increase in corticospinal efficiency that reduces the neural resources needed to perform the task during which measurements are obtained.…”
Section: Discussioncontrasting
confidence: 66%
“…9 However, the lack of correlation between changes in maximal force and CSE of the corresponding limb (either trained or untrained) agrees with previous reports of the absence of correlation between CSE and performance in ballistic contractions 40 and casts doubts about the role of CSE as a mechanism contributing to force increases. It is possible that force increases may be related to adaptations in other descending tracts with a role in force generation, 37 like the reticulospinal tract, 41,42 which could not be detected by TMS of the motor cortex, or in motor cortex structures involved in other TMS outcomes not tested in the present study (ie, changes in intracortical circuits). 17,36 The present study has some limitations that could have influenced the results or limited the conclusions.…”
Section: Discussionmentioning
confidence: 86%
“…A meta-analysis reported that FW RE is not superior to traditional RE for strength improvements [45], which corroborate our findings. Nevertheless, the difference in 1RM squat strength between the BFW and the FW group in our study is likely an effect of test specificity where the exercise performed by the BFW group was isotonic to the test; this is shown previously for the squat exercise [46]. Consequently, we urge for cautious interpretation when comparing 1RM gains between the BFW and FW group.…”
Section: Discussionmentioning
confidence: 50%
“…However, M max has also been shown to remain unchanged following short-term resistance training (≤7 weeks; Refs. 3,17,21,51), despite a study of similar duration showing increases in conduction velocity (12), suggesting that increased conduction velocity of motor units might not necessarily be related to increased M max amplitude in the context of resistance training.…”
Section: Long-term Resistance-trained Individuals Exhibit Greater Maximal Compound Action Potential Amplitudementioning
confidence: 91%